Bacteriological load of the fishes Cynoscion squamipinnis and Lutjanus gutattus in the marketing chain, Costa Rica - Marín, Carolina (2009)
To determine the bacteriological quality of fishery products in the different stages from commercialization, monthly samples were taken during March 2004 and February 2006 from a Costa Rica marketing chain. Microbiological analyses were made to determine total coliforms (CT), faecal coliforms (CF), Escherichia coli (EC), aerobic total count (RTA), Salmonella sp., Staphylococcus aureus, Vibrio cholerae and Vibrio parahaemolyticus. Three body zones were analyzed: skin, belly and muscle. There were differences in the amount of CT between parts: skin had the highest counts, 11% of samples were identified as E. coli. and 2.5% of total counts were higher than the legal limit. Only 1.3% of the samples were S. aureus-positive. Salmonella sp., V. cholerae and V. parahaemolyticus were absent.